The Effect of Transformational and Transactional Leadership Styles on Organizational Readiness for Change Among Health Professionals - Mathewos Mekonnen MSc; Zelalem Bayissa PhD (SAGE Publishing, 2023)
Objective The purpose of this study was to determine the effect of transformational and transactional leadership styles on organizational readiness for change among health professionals in the case of selected public hospitals in the North Showa Zone, Oromia Region, Ethiopia. Methods The institutional-based cross-sectional study design was employed for one month in April 2021. The data were collected from a sample of 212 subordinate health professional staffs. Multi-factor leadership surveys and organizational readiness for change questionnaires were used for data collection. Data were analyzed using descriptive statistics and exploratory factor analysis, run on the SPSS 23 version. Pearson correlation and multiple regressions were used. Multiple regression results were expressed using the statistical values R 2 and β-coefficient. Statistical significance was declared at a P -value of <.05. Result The Pearson product correlation of organizational readiness for change was found to be low positive and statistically significant for both transformational leadership behavior ( r  = .49, P  < .01) and transactional leadership behavior ( r  = .39, P  < .01). Both transformational leadership behavior ( t  = 5.32, P  = .00) and transactional leadership behavior ( t  = 2.08, P  = .034) were found to be significant contributors to the variance of organizational readiness for change among health professionals, according to the findings. However, transformational leadership behavior style appears to make a more significant contribution (β = 0.39) than transactional leadership style (β = 0.15) in predicting organizational readiness for change among health professionals. Conclusion The study revealed that whenever transformational and/or transactional leadership behaviors are exhibited by the administrative staff, readiness for organizational change (commitment and efficacy) increases among health professionals. The study also concluded that a quarter of the readiness for organizational change can be affected by the two leadership styles.